A Study of the Impact of Perceived Corporate Social Responsibility on Employees' Green Innovation Behavior : A Mediating Effect Based on Organizational Culture - Li, Xiaoyang (Transactions on Economics, Business and Management Research, 2024)
Economic development and environmental protection have always been an intractable conflict. In the process of enterprise development, motivating employees' green innovation behavior (GIB) becomes an important strategy for enterprises to realize green development and fulfill their social responsibility. This study takes the relationship between Perceived Corporate Social Responsibility(PCSR) and Employees' Green Innovation Behavior (GIB) as the research object to explore the mechanism of PCSR on Employees' GIB under the mediating effect of organizational culture. 407 corporate employees from various companies in China were surveyed using a questionnaire in this study. The study's findings indicate that the impact of employees' PCSR on their GIB is significant. At the same time, organizational culture serves as a mediator between employees' PCSR and GIB, in which development-oriented organizational culture exerts a significant influence on PCSR and employees' GIB, and economic-oriented organizational culture has no significant impact on PCSR and employees' GIB. This study's findings have significant theoretical and practical implications for comprehending the drivers of employees' GIB and for enhancing employees' GIB through building organizational culture.